Granadan Reflections - Hirschkind, Charles (Material religion, 2016)
This paper explores a practice of historical reflection grounded in the city of Granada's aesthetic and architectural heritage. From the publication of Washington Irving's Tales of Alhambra, in 1823, up through today, Granada has been a highly celebrated destination for travelers and tourists, drawn by the sublimity of its romantic oriental splendor. Yet, although the city is well known for the Orientalist fantasy it puts on display for touristic consumption, here I consider a form of reflection that cannot be encompassed within the protocols of discourse and experience mobilized by the tourist industry, and that indeed, may challenge those protocols and the assumptions about history and geography they entail. Specifically, drawing on the work of the late-nineteenth-century Spanish writer, Angel Ganivet, I trace a tradition of reflection that engages the city's unique sensory and architectural configuration as the basis from which to reassess Spain's relation to both Islam and Europe. I conclude with some general observations on the way the sensory and material infrastructure of Moorish Spain mediates and conditions the possibilities of finding a place for Islam in the country today.